2006
DOI: 10.1158/1078-0432.ccr-05-1257
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Antigen Recognized by the 22-1-1 Monoclonal Antibody Encourages Colorectal Cancer Progression under the Scanty CD8+ T Cells

Abstract: Purpose:The receptor-binding cancer antigen expressed on SiSo cells (RCAS1) is a novel tumorassociated antigen. Although evidence suggests that RCAS1 suppresses immunity by inducing tumor-infiltrating lymphocyte (TIL) apoptosis, RCAS1function in humans is controversial. RCAS1 overexpression leads to the generation of theTn glycan antigen (N-acetyl-D-galactosamine, GalNAc) recognized by the 22-1-1monoclonal antibody. The objective of this study is to examineTn glycan antigen function in colorectal cancer and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Interestingly, RCAS1 expression has been found more frequently in tumors with reduced or abnormal E-cadherin expression, thereby supporting evidence that both proteins may be critical for the mechanism of metastasis and recurrence in human colorectal cancer [13]. In addition, RCAS1 overexpression has been shown to induce the generation of the TN glycan antigen (N-acetyl-D-galactosamine, GalNAc) which, in the presence of scanty numbers of CD8 + T cells, may be a risk factor for the development of multiple liver metastases as well as being an independent prognostic factor for colorectal cancer [29]. Accordingly, RCAS1 expression was significantly correlated with the depth of invasion, lymph node metastasis, and histological stage in patients with esophageal carcinoma [15].…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, RCAS1 expression has been found more frequently in tumors with reduced or abnormal E-cadherin expression, thereby supporting evidence that both proteins may be critical for the mechanism of metastasis and recurrence in human colorectal cancer [13]. In addition, RCAS1 overexpression has been shown to induce the generation of the TN glycan antigen (N-acetyl-D-galactosamine, GalNAc) which, in the presence of scanty numbers of CD8 + T cells, may be a risk factor for the development of multiple liver metastases as well as being an independent prognostic factor for colorectal cancer [29]. Accordingly, RCAS1 expression was significantly correlated with the depth of invasion, lymph node metastasis, and histological stage in patients with esophageal carcinoma [15].…”
Section: Discussionmentioning
confidence: 59%
“…In colorectal cancer, there were 44 papers assessing CD8 [13,30,37,39,70,71,[81][82][83]85,86,92,93,98,108,109,112,114,116,117,121,122,125]. Of the nine studies that directly compared intratumoural CD8 assessment: three studies (625 patients) found IE significant where ST was not [75,81,121]; two studies (460 patients) found ST significant where IE was not [83,125]; three studies (1294 patients) found both IE and ST to be significant [71,85,98]; and one (291 patients) study compared IE assessment with combined assessment of IE and ST and found IE alone to be significant [37].…”
Section: Cd8 (Cytotoxic T-cells)mentioning
confidence: 99%
“…Fifteen independent studies (5475 patients) used an electronic method of assessment [13,59,82,83,85,86,[91][92][93]109,111,[117][118][119][120], of which 11 (4949 patients) found CD8 to be significant for survival [13,82,83,85,86,92,93,109,[117][118][119]. Twenty-two independent studies (5534 patients) used a manual method of assessment [9,30,37,39,70,71,81,84,88,89,98,108,110,[112][113][114][115][116][121][122][123]125], of which 16 (4689 patients) found CD8 to be significant for survival…”
Section: Cd8 (Cytotoxic T-cells)mentioning
confidence: 99%
See 1 more Smart Citation
“…( 7,8 ) Immunohistochemical studies with tissue samples revealed that RCAS1 expression has been correlated significantly with poor overall survival in patients with several malignancies. ( 9–11 ) Ogushi et al . ( 12 ) provided the first in vivo evidence that EBAG9 was a tumor‐promoting and prognostic factor for renal cell carcinoma.…”
mentioning
confidence: 99%